HANDLING SPIRITUALISM SEBAGAI KONTROL DIRI PADA REMAJA DI PONDOK PESANTREN - Fitriyah, Lailatul; Wahyuni, Erfi Fitri (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
This study presents awareness about attitudes towards pesantren teenagers who begin to assume the small degree of scale of regulation in pesantren. Spiritual education becomes a shield for adolescent boarding schools to be able to control themselves so as not to make deviations (violations) that have become written or unwritten provisions. The research method used is a qualitative with case study. The results showed that the relevance of spirituliasm education is able to be one of the enlightenment drugs for the storage of pesantren regulations. Adolescent boarding schools are able to realize the form of mistakes, through the handling carried out by pesantren parties such as: duha prayer activities, tahajjud prayers, exemplary teachers, teacher age, and the application of classical books. The customization can have a synergic impact on the students both physically and spiritually to be able to take ibroh and understand the meaning of pesantren regulations in accordance with the goals set. So that's when a person who is faithful, intellectual, and useful to society is formed.